RFI Suppression in Ultrawideband SAR Using an Adaptive Line Enhancer - Vu, Viet T; Sjögren, Thomas K; Pettersson, Mats I; Håkansson, Lars; Gustavsson, Anders; Ulander, Lars M H (IEEE geoscience and remote sensing letters, 2010)
In this letter, we propose an approach to suppress radio-frequency interference (RFI) in ultrawideband (UWB) low-frequency synthetic aperture radar (SAR). According to the proposal, RFI is suppressed by using an adaptive line enhancer controlled by the normalized least mean square algorithm. The approach is tested successfully on real UWB low-frequency SAR data. In order to keep the computational burden down, possible ways to integrate the RFI suppression approach into SAR imaging algorithms are also suggested.